Analisis determinan kepuasan Konsumen: Peran value chain, service quality dan web quality - Taufik, Henry Meytra; Pribadi, Agis Teguh (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The development of online shopping platforms is increasing day by day. This is evidenced by the many online stores. Shopee is a commercial online site in Indonesia that provides a variety of appealing offers to its customers, ranging from discounted shipping costs to discounted food prices. The purpose of this study is to find out how much influence the value chain, service quality, and web quality have on customer satisfaction in the Shopee application. This type of research uses a quantitative approach. The sample in this study was 170 consumer respondents, and we used multiple linear regression. The results show that the three variables (value chain, service quality, and web quality) have an effect on customer satisfaction. These results show that the hypothesis of the three variables can be accepted. In addition, this research can also provide very good input for the development of the Shopee application business. Limitations in research This means that the number of respondents obtained was 170, and the survey was carried out at Sultan Ageng Tirtayasa University. It is recommended that further research be done to increase the significance of sampling by expanding the sample size and conducting surveys in a wider geographical area.